A review of bio-fuelled LHR engines. Issue 1 (31st December 2022) - Pandey, Krishna Kumar; Murugan, S.
Abstract : Biofuels are expected to play an important role in heat and power applications in the near future. Despite a lot of improvements took place in compression ignition (CI) engine technology, the thermal efficiency of a CI engine is still found to be lesser than 40% in a conventional diesel-fuelled engine which is mainly due to the heat loss from the engine. Preventing heat loss from CI engines by adopting low heat rejection (LHR) engine technology has been focused for many years. Since the introduction of biofuels, there have been significant research works carried out on the utilisation of different biofuels in LHR engines. This paper presents a comprehensive review on the different coating methods and coating materials used for developing LHR engines, thermomechanical analysis of biofuelled LHR engines, assessment of the performance, emission and combustion parameters of different categories of LHR engines. Abbreviations: BD: Biodiesel; BR: Blending Ratio; BSFC: Brake Specific Fuel Consumption; BTE: Brake Thermal Efficiency; CI: Compression Ignition; CM: Coating Material; CO: Carbon Monoxide; CT DEE: Coating Thickness Diethyl Ether; D-Gun: Detonation Gun; DOA: Degree of Adiabacity; EGR: Exhaust gas circulation; EGT: Exhaust Gas Temperature; HC: Hydrocarbon; HVOF: High-velocity oxy-fuel; IC: Internal Combustion; LHR: Low Heat Rejection; NOx : Oxides of Nitrogen; PVD: Physical Vapour Deposition; SEM: Scanning Electron Microscopy; SI: Spark Ignition; TBC: Thermal Barrier Coating; TMF: Thermal Mechanical Fatigue; WCO: Waste Cooking Oil; XRD: X-ray Diffraction; YSZ: Yttria-Stabilised Zirconia